Ebola impact on african health systems entails a quest for more international and local resilience: the case of african portuguese speaking countries - Lapão, Luís Velez (2015)
Introduction: Ebola epidemics have shown to have significant impacts on many aspects of healthcare systems. African countries have been facing many difficulties while addressing Ebola epidemics, moreover due to both lack of resources and fragmented involvement of national and international entities. The participation of multiple organizations has created serious problems of coordination of aid and the operation of that aid on the ground. This paper aims at addressing the impact of Ebola epidemics on African health systems, with a special focus on the definition of impact mitigation guidelines and the role of resilience. The example of Portuguese speaking countries is presented. Methods: a combination of literature review and case study methods are used. A literature review on Ebola outbreak impact on health systems will provide information to define a set of guidelines for healthcare services response to Ebola. The role of cooperation in providing additional resilience is described. Finally a case study focusing on the Portuguese collaboration and intervention in African Portuguese Speaking Countries (PALOP) is presented, as an example how the international community can provide additional resilience. Results: the existing knowledge is very helpful to guide both the preparation and the coordination of Ebola preparedness interventions. Additional resilience can be provided by international cooperation. Conclusion: in addition to international concrete support in times of crisis, to have a regional strategy of creating (multi-national) teams to rapidly implement an intervention while establishing better regional capacity to have sufficient resources to support the “resilience” required of the health system.